1999
DOI: 10.1002/(sici)1097-0142(19991215)86:12<2674::aid-cncr12>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Report from the International Union Against Cancer (UICC) Tumor Biology Committee

Abstract: At this workshop, clinicians active in the use of dendritic cells all expressed the need to have an available supply of interleukin (IL)‐4. There was discussion that unless some institution, such as the National Cancer Institute of the U.S., took action, a stable commercial source of IL‐4 might not be available in the future. The UICC leadership is currently looking into this matter. See also pages 2593–6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Doses of up to 1 ϫ 10 9 antigen-pulsed DC have been administered in cancer patients without occurrence of major side effects. Correlations between duration of immune response and numbers of administered DC have been seen in human and animal studies (15). It has remained a matter of debate whether DC derived from CD34 ϩ precursor cells or monocyte-derived DC should be preferentially used in clinical vaccination protocols.…”
Section: Dendritic Cell Immunotherapymentioning
confidence: 99%
“…Doses of up to 1 ϫ 10 9 antigen-pulsed DC have been administered in cancer patients without occurrence of major side effects. Correlations between duration of immune response and numbers of administered DC have been seen in human and animal studies (15). It has remained a matter of debate whether DC derived from CD34 ϩ precursor cells or monocyte-derived DC should be preferentially used in clinical vaccination protocols.…”
Section: Dendritic Cell Immunotherapymentioning
confidence: 99%
“…Consistent with this, some investigators [72±75] have reported difficulties in generating [76] monocyte-derived DCs (Mo-DCs) in cancer patients, whereas others have not [73]. Cancers may also influence DC production at an even earlier level and vascular endothelial growth factor (VEGF) has been suggested to suppress DC production in the bone marrow [77].…”
Section: In Human Cancermentioning
confidence: 99%